Comparative analysis of social issues toward medical abortion using mifepristone in South Korea and the United States: Topic modeling and sentiment analysis - Minoh Ko; Dong-Young Park; Jung Mi Oh; Yun-Kyoung Song (PLoS ONE, 2026)
This study aimed to compare social issues influencing the use of mifepristone for medical abortion between South Korea and the United States by analyzing media coverage through text mining techniques. News articles published between 2006 and 2022 related to mifepristone were collected using web scraping from representative news platforms in both countries. The collected data underwent preprocessing, followed by text analysis using the bag-of-words model. Topic modeling was conducted through Latent Dirichlet Allocation, and sentiment analysis involved using the lexicon-based methods specific to Korean and English texts. Analysis of 7,938 Korean and 650 United States articles revealed distinct patterns in media discourse on mifepristone and medical abortion. The United States coverage was polarized, encompassing clinical, legal, and access-related debates, whereas Korean articles prioritized access barriers, safety concerns, and the urgency for domestic approval, reflecting predominantly negative sentiments related to cultural stigma. This study highlights differences in the media portrayals and public perceptions of mifepristone between South Korea and the United States, underscoring the influence of regulatory contexts, public concerns and cultural attitudes on medical abortion discourse.